Protective Effect of miR-204 on Doxorubicin-Induced Cardiomyocyte Injury via HMGB1 - Du, Youyou (Oxid Med Cell Longev, 2020)
The toxicity of doxorubicin (DOX) limits its clinical application. Nevertheless, at present, there is no effective drug to prevent DOX-induced cardiac injury. miR-204 is a newly discovered miRNA with many protective effects on cardiovascular diseases. However, little research has been done on the effects of miR-204 on DOX-induced cardiac injury. Our study is aimed at investigating the effect of miR-204 on DOX-induced myocardial injury. An adenoassociated virus system was used to achieve cardiac-specific overexpression of miR-204. Two weeks later, the mice were intraperitoneally injected with DOX (15 mg/kg) to induce cardiac injury. H9c2 myocardial cells were used to validate the role of miR-204 in vitro. Our study showed that miR-204 expression was decreased in DOX-treated hearts. miR-204 overexpression improved cardiac function and alleviated cardiac inflammation, apoptosis, and autophagy induced by DOX. In addition, our results showed that miR-204 prevented DOX-induced injury in cardiomyocytes by directly decreasing HMGB1 expression. Moreover, the overexpression of HMGB1 could offset the protective effects of miR-204 against DOX-induced cardiac injury. In summary, our study showed that miR-204 protected against DOX-induced cardiac injury via the inhibition of HMGB1, and increasing miR-204 expression may be a new treatment option for patients with DOX-induced cardiac injury.